Albendazole Degradation Possibilities by UV-Based Advanced Oxidation Processes. (20th December 2018) - Ljubas, Davor; Čizmić, Mirta; Vrbat, Katarina; Stipaničev, Draženka; Repec, Siniša; Ćurković, Lidija; Babić, Sandra
Abstract : Pharmaceuticals are present in an aquatic environment usually in low (ng/L) concentrations. Their continuous release can lead to unwanted effects on the nontarget organisms. The main points of their collection and release into the environment are wastewater treatment plants. The wastewater treatment plants should be upgraded by new technologies, like advanced oxidation processes (AOPs), to be able to degrade these new pollutants. In this study, the degradation of albendazole (ALB), a drug against parasitic helminths, was investigated using four UV-based AOPs: UV photolysis, UV photocatalysis (over TiO2 film), UV + O3, and UV + H2 O2 . The ranking of the degradation process degree of the ALB and its degradation products for studied processes is as follows: UV photolysis < UV photocatalysis with TiO2  < UV + O3  < UV + H2 O2 . The fastest degradation of ALB and its degradation products was obtained by UV-C + H2 O2 process with a degradation efficiency of 99.95%, achieved in 15 minutes.